2016
DOI: 10.1017/s0022215116008008
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the evidence base for vidian neurectomy in managing rhinitis

Abstract: Endoscopic vidian neurectomy does have a role in the surgical management of refractory rhinitis, particularly in patients with non-allergic rhinitis, but a well-designed cohort trial would be advantageous to clarify long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 49 publications
3
45
1
Order By: Relevance
“…Interestingly, our experience parallels that reported in the literature on functional outcomes of vidian neurectomy for incoercible rhinitis. A recent review analyzing 16 studies reported a dry eye condition in 23.96% (276/1,152) of patients . A subanalysis limited to eight studies, also addressing the duration of dry eye symptoms, found that they were temporary in 96.46% of patients (218/226) and spontaneously resolved within 6 months …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, our experience parallels that reported in the literature on functional outcomes of vidian neurectomy for incoercible rhinitis. A recent review analyzing 16 studies reported a dry eye condition in 23.96% (276/1,152) of patients . A subanalysis limited to eight studies, also addressing the duration of dry eye symptoms, found that they were temporary in 96.46% of patients (218/226) and spontaneously resolved within 6 months …”
Section: Discussionmentioning
confidence: 99%
“…review analyzing 16 studies reported a dry eye condition in 23.96% (276/1,152) of patients. 13 A subanalysis limited to eight studies, also addressing the duration of dry eye symptoms, found that they were temporary in 96.46% of patients (218/226) and spontaneously resolved within 6 months. 13 The analysis of sensitivity impairment provided more complex results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of endoscopic skull‐base surgery combined with improved understanding of the anatomy and function of the vidian nerve has led to a resurgence of interest in the procedure of vidian neurectomy . The procedure was very popular in the 1970s and 1980s before it lost favor because of reports of complications and questions regarding long‐term efficacy .…”
Section: Vidian Neurectomymentioning
confidence: 99%
“…Vidian neurectomy has been described for treating symptoms of allergic, nonallergic, and mixed rhinitis refractory to medical therapy . In particular, several authors describe its utilization in intractable vasomotor rhinitis, a form of chronic rhinitis that is characterized by watery rhinorrhea presumed to be resulting from an imbalance of parasympathetic and sympathetic input to the nose .…”
Section: Vidian Neurectomymentioning
confidence: 99%